Host–parasite relationships between seabirds and the haemadipsid leech Chtonobdella palmyrae (Annelida: Clitellata) inhabiting oceanic islands in the Pacific Ocean. Issue 14 (18th December 2020) - Nakano, Takafumi; Suzuki, Hajime; Suzuki, Naoko; Kimura, Yuichi; Sato, Tatsuo; Kamigaichi, Hiromi; Tomita, Naoki; Yamasaki, Takeshi
Abstract: The duognathous haemadipsid leeches of the genus Chtonobdella show a trans-oceanic distribution throughout the Indo-Pacific region. Although passive long-distance dispersal (LDD) of Chtonobdella leeches by birds has been suggested, little is known about the host–parasite relationships between avian hosts and Chtonobdella leeches. In the current study, we investigated Chtonobdella leech infestations of the eyes and other mucus membranes of migratory procellariiform seabirds, Pterodroma hypoleuca and Oceanodroma tristrami, captured at six locations in the Bonin Islands, Honshu and Okinawa Island, Japan. Analyses of the partial sequences of 18S rRNA, 28S rRNA, and mitochondrial cytochrome c oxidase subunit I (COI) and morphological examination of the specimens demonstrated that the Chtonobdella leeches belonged to Chtonobdella palmyrae, which is indigenous to Palmyra Atoll in the Northern Line Islands. A dominant COI sequence type was observed in samples from all six sites; therefore, C. palmyrae almost surely dispersed approximately 1000 km by infesting the eyes and mucus membranes of procellariiform seabirds. The host–parasite relationships between procellariiform seabirds and C. palmyrae provide explicit evidence of the LDD of duognathous haemadipsid leeches. The taxonomic status of Haemadipsa zeylanica ivosimae from the Volcano Islands is also briefly discussed.